PERENCANAAN JADWAL INDUK PRODUKSI DENGAN MENGGUNAKAN LINIER PROGRAMMING PADA INDUSTRI MANUFAKTUR PT â€Xâ€ - Nurcahyo, Yusuf Eko (Heuristic, 2015)
The fluctuated demand is one of constrain in planning and scheduling process because it affects the cost of production and inventory costs incurred. PT "X" is a sandal maker manufacturing industry that produces sandals and slippers men women. In the manufacture of slippers companies often do not correspond to the amount of consumer demand, so common advantages and disadvantages of production quantities. Master production scheduling (MPS) is a solution to overcome the problem of making sandals to avoid excess and shortage of production of slippers. To create a Master Production Schedule first made a forecast for the next planning period is 5 months of January, February, March, April, May and June.Keyword: Master Production Schedule, linier programming